The Human IL-22 Receptor Is Regulated through the Action of the Novel E3 Ligase Subunit FBXW12, Which Functions as an Epithelial Growth Suppressor - Joseph Franz; Jacob Jerome; Travis Lear; Qiaoke Gong; Nathaniel M. Weathington (Journal of Immunology Research)
Interleukin- (IL-) 22 signaling is protective in animal models of pneumonia and bacteremia by Klebsiella pneumoniae and mediates tissue recovery from influenza and Staph aureus infection. We recently described processing of mouse lung epithelial IL-22 receptor (IL-22R) by ubiquitination on the intracellular C-terminal. To identify cellular factors that regulate human IL-22R, we screened receptor abundance while overexpressing constituents of the ubiquitin system and identify that IL-22R can be shuttled for degradation by multiple previously uncharacterized F-box protein E3 ligase subunits. We observe that in human cells IL-22R is destabilized by FBXW12. FBXW12 causes depletion of endogenous and plasmid-derived IL-22R in lung epithelia, binds the E3 ligase constituent Skp-1, and facilitates ubiquitination of IL-22R in vitro. FBXW12 knockdown with shRNA increases IL-22R abundance and STAT3 phosphorylation in response to IL-22 cytokine treatment. FBXW12 shRNA increases human epithelial cell growth and cell cycle progression with enhanced constitutive activity of map kinases JNK and ERK. These findings indicate that the heretofore-undescribed protein FBXW12 functions as an E3 ligase constituent to ubiquitinate and degrade IL-22R and that therapeutic FBXW12 inhibition may enhance IL-22 signaling and bolster mucosal host defense and infection containment.